2001
DOI: 10.1097/00129492-200105000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Choristoma of the Middle Ear: A Component of a New Syndrome?

Abstract: Eighty-six percent of the reported patients with choristoma have three or four of the four criteria listed to designate middle ear salivary choristoma as part of a syndrome. In the remaining four patients, all of the structures were not assessed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
4

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 18 publications
1
20
0
4
Order By: Relevance
“…[6,7] A study by Buckmiller has demonstrated heterotopic salivary gland in middle ear [8] and in addition Buckmiller et al have suspected the presence of ectopic salivary tissue in middle ear as a component of new syndrome. [8] Other reported sites of involvement are anterior chest wall, cerebellopontine angle, stomach, parathyroid gland, lacrimal gland, pterygopalatine fossa, tonsils, sella turcica, thyroid, mediastinum, rectum, vulva, prostate, gingival, mandible, maxilla, and posterior triangle of the neck. [6,9] In our case, heterotopic salivary gland was found as 3-4 tissue tags on left tonsillar walls.…”
Section: Discussion With Brief Review Of Literaturementioning
confidence: 99%
“…[6,7] A study by Buckmiller has demonstrated heterotopic salivary gland in middle ear [8] and in addition Buckmiller et al have suspected the presence of ectopic salivary tissue in middle ear as a component of new syndrome. [8] Other reported sites of involvement are anterior chest wall, cerebellopontine angle, stomach, parathyroid gland, lacrimal gland, pterygopalatine fossa, tonsils, sella turcica, thyroid, mediastinum, rectum, vulva, prostate, gingival, mandible, maxilla, and posterior triangle of the neck. [6,9] In our case, heterotopic salivary gland was found as 3-4 tissue tags on left tonsillar walls.…”
Section: Discussion With Brief Review Of Literaturementioning
confidence: 99%
“…Heterotopia involving the salivary gland is found in the various sites of the head and neck including the lower neck [2,3], anterior chest wall [4], gingiva [5] and middle ear [6][7][8][9][10]. Thus, it can be added in the differential diagnosis of the middle ear cavity masses presenting unilateral hearing loss without perforation of the tympanic membrane, which usually include congenital cholesteatoma, glomus tumor, neuroma, dermoid cyst, teratoma and lymphoma.…”
Section: Discussionmentioning
confidence: 99%
“…Choristoma of the middle ear frequently presents as a mass behind the tympanic membrane situated in the posterosuperior quadrant often associated with ossicular and facial nerve anomalies ( middle ear involvement [13]. It has been proposed by Buckmiller et al [33] that choristoma of the middle ear may represent a component of a new syndrome along with unilateral hearing loss, abnormalities of the incus and/or stapes, and anomalies of the facial nerve. The authors observed that 86% of the reported patients with choristoma have 3-4 of the 4 criteria listed to designate middle ear salivary choristoma as part of a syndrome.…”
Section: Clinical Featuresmentioning
confidence: 99%